The Transformation of the Javanese Patrimonial-feudalistic Bureaucracy from the Traditional Kingdom to the Dutch Colonial Period (Forum Ilmu Sosial, 2022)
This article aims to analyze the history of the continuity of the Javanese bureaucratic model from the classical period to the Dutch colonial period. The method used is the historical method using secondary historical sources. The results show that the bureaucracy in Indonesia is the product of a long historical experience originating from Javanese culture. It was born from a bureaucracy that was initially a traditional feudal bureaucracy which was later assimilated into a rational, legal western bureaucracy that implemented this bureaucracy for almost a century under "beamtenstaat", state officials. Western bureaucracy does not necessarily eliminate the tradition of feudal-patrimonial bureaucracy but instead synergizes in the form of a feudal Colonial bureaucracy.